1995
DOI: 10.1007/bf00199641
|View full text |Cite
|
Sign up to set email alerts
|

Duplex-Doppler evaluation of intestinal peristalsis in patients with bowel obstruction

Abstract: Duplex-Doppler was used to visualize intestinal peristalsis in 30 patients with intestinal distension. The series included 12 patients with acute mechanical obstruction, 13 with long-standing mechanical obstruction, and five with paralytic ileus. The Duplex-Doppler recordings showed several patterns characterized by different degrees of intensity and frequency of the signals according to the type of obstruction, its duration, and the site of Doppler sampling relative to the obstructed segment. Duplex-Doppler e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Ultrasonography is a real-time dynamic imaging technique, and provides the opportunity to visualise the functional effects of intestinal contractions. In man, ultrasonography has been shown to provide qualitative and quantitative data about large and small intestinal peristalsis (Pistor 1989;Gimondo et al 1995;Gimondo and Mirk 1997). Studies in man have shown that ultrasonographic measurements of intestinal motility correlate well with scintigraphy measurements, have good interobserver variation, and are more accurate than electrical activity measurements (Irvine et al 1 9 9 3 ; P f a ffenbach et al 1995; Benini et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasonography is a real-time dynamic imaging technique, and provides the opportunity to visualise the functional effects of intestinal contractions. In man, ultrasonography has been shown to provide qualitative and quantitative data about large and small intestinal peristalsis (Pistor 1989;Gimondo et al 1995;Gimondo and Mirk 1997). Studies in man have shown that ultrasonographic measurements of intestinal motility correlate well with scintigraphy measurements, have good interobserver variation, and are more accurate than electrical activity measurements (Irvine et al 1 9 9 3 ; P f a ffenbach et al 1995; Benini et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in man have shown that ultrasonographic measurements of intestinal motility correlate well with scintigraphy measurements, have good interobserver variation, and are more accurate than electrical activity measurements (Irvine et al 1 9 9 3 ; P f a ffenbach et al 1995; Benini et al 1999). Ultrasonography has therefore been used in man for some time to assess intestinal m o t i l i t y, both to identify regions of the intestine, and to document normal and abnormal peristalsis (Daggett 1974;Pistor 1989;Gimondo et al 1995). Ultrasonography is now widely used to evaluate normal intestinal function and different disease states, and to determine the effects of motility modifying drugs (Daggett 1974;Pistor 1989;Gimondo et al 1995;Huang et al 1 9 9 5 ;Dumitrascu et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fur die Unterscheidung von mechanischem und paralytischem Ileus ist der Nachweis der bereits primar dilatierten Dunn-und Dickdarmschlingen sowie der prirnar fehlenden Peristaltik entscheidend [24]. Differentialdiagnostisch ist auch an die intestinale Pseudoobstruktion (Olgilvie Syndrom) mit ihren vielen unterschiedlichen Ursachen zu denken [25].…”
Section: Klinik Und Pathophysiologieunclassified